ANALISIS PERBANDINGAN TINGKAT KEPATUHAN WAJIB PAJAK SEBELUM DAN SESUDAH PENERAPAN PROGRAM PENGUNGKAPAN SUKARELA (STUDI KASUS PADA WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KPP PRATAMA JEMBER) - Fitri, Ayu Ningratul; Dimyati, Muhaimin; Sari, Nurshadrina Kartika (RISTANSI: Riset Akuntansi, 2024)
This study aims to examine the differences in taxpayer compliance levels before and after the implementation of the Voluntary Disclosure Program, focusing on moral obligations, timely reporting, taxpayer honesty, tax understanding, and tax penalties at the KPP Pratama Jember. The sample consists of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using validity, reliability, normality, homogeneity tests, paired T-test, and ANOVA. The results reveal significant differences in taxpayer compliance levels between the periods before and after the implementation of the program across all factors examined. Additionally, simultaneous analysis indicates that these factors collectively influence taxpayer compliance. This study supports the Compliance Theory and the Theory of Planned Behavior, highlighting that incentives, penalties, and taxpayers’ positive attitudes toward taxation are key factors in improving compliance. These findings provide strategic implications for enhancing the effectiveness of tax policies in the future.